Hubungan Kompetensi Pedagogik Guru Dengan Hasil Belajar Matematika Kelas Tinggi di Sekolah Dasar - Musfirah Musfirah; Hasnah Hasnah; Rezki Amalia (Universtas Negeri Makassar, 2022)
This study aims to determine whether there is a relationship between teacher pedagogic competence and high grade students' mathematics learning outcomes at UPT SD Negeri 8 Rappang, Sidenreng Rappang Regency. This research uses a quantitative approach with the type of correlation research. The results showed that there was a significant relationship between teacher pedagogic competence and students' mathematics learning outcomes, for class VI (six) where rcount = -0.149 while rtable with a significant level of 5% = 0.423 and a significant level of 1% = 0.537, for class V where rcount = -0.149 while rtable with a significant level of 5% = 0.423 and a significant level of 1% = 0.537, and for class IV where rcount = -0.357 while rtable with a significant level of 5% = 0.532 and a significant level of 1% = 0.661. So the conclusion of this study is that the pedagogic competence of teachers has a significant relationship with high grade mathematics learning outcomes at SDN 8 Rappang, Sidrap Regency.